Pesantren, Islamic Studies, and Ecological Discourse: Eco-pesantren study in Pesantren Hanacaraka Wonogiri, Central Java - Mibtadin, Mibtadin (Proceeding International Conference on Religion, Science and Education, 2023)
Environmental issues receive serious attention from all social elements. Until now, environmental damage is still ongoing which can be fatal to all life (sagunging dumadi). In Islamic studies it is known as environmental jurisprudence (fiqh al-bi’ah). This jurisprudence seeks to foster environmental awareness through environmental education can contribute to preventing further environmental damage and even repairing it. Environmental education is an effort to grow and increase awareness of community elements to behave environmentally friendly so that the sustainability of the ecosystem is maintained (al-hifdz al-’alam). One of them is through the eco-pesantren education approach, an educational model that seeks to produce students who have a balanced knowledge supply between worldly science and ukhrowi, both as ’abdullah and khalifatullah fil’ardh. Education at Pesantren Hanacaraka puts forward the terminology al-tarbiyah meaning to maintain and educate in applying the concept of Islam as a religion of rahmatan lil’alamin to preserving nature (memayu hayuning bawana). Eco-pesanten-based education is an activity to make pesantren environmentally friendly through activities such as improving environmentally friendly lifestyles, developing health and environmental units in pesantren, including environmental curriculum in pesantren and taking concrete actions in waste management, clean water, and sanitation, which can be used as role models and learning for the supporting communities of pesantren. Pesantren Hanacaraka with an eco-pesantren education model is expected to produce students who have a sense of having (handarbeni) and hangrungkebi environment based on spiritual attitudes.